Efeitos do citrato de fentanila em Trachemys dorbigni (Duméril e Bibron, 1835) e Trachemys scripta elegans (Wied, 1839) - Kaminishi, Árthur Paulino Sanzo (2013)
A total of 30 animals have been used, 15 Trachemys dorbigni and 15 Trachemys scripta elegans, with body mass índex ranging from 0.750 to 1.800 kg, from the Wild Animals Research and Education Laboratory (LAPAS). Each species was separated into two groups: an experimental, with 10 animals, and a control, with five animals. It was applied fentanyl citrate 0.05 mg/kg to experimental groups, and physiological solution 1 ml/kg to the control groups, injected subcutaneously (SC), with the purpose of evaluating the effects of this drug and define their analgesic efficiency. The coloring of oral mucosa, cloacal temperature and heart rate, as well as any adverse reaction from pharmacological effects were monitored. For nociceptive stimulus, it was used the mechanical compression shear force of up to 2,000grams over the phalanges, interdigital tissue and the tail end. The 0.05 mg/kg dose caused analgesia in all of the animals, and the effects started 10 minutes after the application and lasted 134 ± 26 minutes and 120 ± 20 minutes for Trachemys dorbigni and Trachemys scripta elegans, respectively. In 80% of the animals there was total absence of reaction to maximum nociceptive stimulus, with an average duration of 39 ± 10 minutes for T. dorbigni and 30 ± 12 minutes for T. scripta elegans. Cyanosis of the oral mucosa was not noticed, and in relation to heart rate and cloacal temperature there were no relevant differences. It is concluded that the protocol of fentanyl citrate 0.05 mg/kg SC is capable of promoting analgesia in Trachemys dorbigni and Trachemys scripta elegans, producing no significant physiological changes that put the animal at risk.